Analysis of Student and Teacher Needs for AR Geometry Media based on Kraton Culture - Fernanda Setya Putra; Muhammad Noor Kholid (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to conduct a systematic needs analysis of elementary school students and teachers as a basis for designing augmented reality (AR) based geometry learning media integrated with Kraton culture.Methodology: This descriptive qualitative study involved 22 fourth and fifth grade students and two teachers at SD Negeri 2 Pandean. Data were collected through a questionnaire, semi-structured teacher interviews, classroom observations, and document analysis. Thematic analysis was used, and descriptive statistics were applied to closed items. Results: Students have trouble visualizing how nets relate to solid figures with static images. They need AR features such as manipulable 3D models that can be rotated and explored. Animations that unfold and refold solid figures, along with clear highlights of faces, edges, and vertices, aid comprehension. Step by step guidance, interactive short quizzes with instant feedback, and examples connecting geometry to Kraton architecture are also needed. Teachers see potential in AR media if it offers a dedicated teacher mode, explicit usage guidelines, concise lesson segments, compatibility with mid-range devices, offline access, and a curriculum aligned balance between cultural and standard content.Applications/Originality/Value: This study provides context-sensitive and practical design guidelines for developing AR geometry learning media that address students’ spatial visualization difficulties, align with curriculum demands, and are feasible for elementary school contexts with limited technological infrastructure.